Primary triage nurses do not divert patients away from the emergency department at times of high in-hospital bed occupancy - a retrospective cohort study. Issue 1 (December 2016) - Blom, Mathias; Erwander, Karin; Gustafsson, Lars; Landin-Olsson, Mona; Jonsson, Fredrik; Ivarsson, Kjell
Abstract Background Emergency department (ED) overcrowding is frequently described in terms of input- throughput and output. In order to reduce ED input, a concept called primary triage has been introduced in several Swedish EDs. In short, primary triage means that a nurse separately evaluates patients who present in the Emergency Department (ED) and either refers them to primary care or discharges them home, if their complaints are perceived as being of low acuity. The aim of the present study is to elucidate whether high levels of in-hospital bed occupancy are associated with decreased permeability in primary triage. The appropriateness of discharges from primary triage is assessed by 72-h revisits to the ED. Methods The study is a retrospective cohort study on administrative data from the ED at a 420-bed hospital in southern Sweden from 2011–2012. In addition to crude comparisons of proportions experiencing each outcome across strata of in-hospital bed occupancy, multivariate models are constructed in order to adjust for age, sex and other factors. Results A total of 37, 129 visits to primary triage were included in the study. 53.4 % of these were admitted to the ED. Among the cases referred to another level of care, 8.8 % made an unplanned revisit to the ED within 72 h. The permeability of primary triage was not decreased at higher levels of in-hospital bed occupancy. Rather, the permeability was slightly higher at occupancy of 100–105 % compared to <95 % (OR 1.09 95 % CI 1.02–1.16). No significant association between in-hospital bed occupancy and the probability of 72-h revisits was observed. Conclusions The absence of a decreased permeability of primary triage at times of high in-hospital bed occupancy is reassuring, as the opposite would have implied that patients might be denied entry not only to the hospital, but also to the ED, when in-hospital beds are scarce.